Patient quality of life determinants in decision-making regarding amputation - Carly Lightstone; Naomi Eisenberg; Sherry Harburn; Dorina Baston; Rima Styra; Graham Roche-Nagle (PLoS ONE, 2026)
Background Psychological adjustment to amputation begins well before surgery and is pivotal in determining both functional and emotional outcomes. For patients with Peripheral Arterial Disease (PAD), understanding their emotional and psychological challenges during the perioperative period is essential for healthcare teams to provide effective support. Addressing these challenges can enhance surgical outcomes and facilitate long-term rehabilitation. As patients approach amputation, their psychological adjustment significantly influences postoperative recovery and quality of life. Surgeons and healthcare teams should integrate psychological considerations into care planning to optimize outcomes and support holistic healing. This study explores the psychological challenges faced by patients with PAD undergoing amputation, providing insights relevant to surgeons in enhancing preoperative care. Methods We conducted a qualitative study with patients who underwent primary elective amputations as part of a vascular surgery inpatient service. Data was collected through semi-structured interviews, which were conducted between five and ten days post-amputation. The interviews were analyzed using Braun and Clarke’s (2006) guidelines for thematic analysis, which allowed for the identification of key patterns and themes related to the psychological adjustment process. Findings Three key themes emerged: Breaking Point , diminished quality of life threshold when patients reached a threshold of suffering from PAD; Meaning Attributed to Amputation , highlighting varied perceptions of the procedure’s impact on quality of life; and Trust in the Healthcare Team , emphasizing the role of effective communication and trust in the patient-provider relationship. Conclusion These findings underscore the importance of addressing emotional and psychological needs of patients in the preoperative period to improve surgical outcomes. By fostering trust, and providing tailored preoperative support, surgeons along with the healthcare team can help better prepare patients to enhance post-operative recovery and reduce anxiety, and negative cognitions. Future research should explore practical effective ways to integrate psychological care into surgical practice, with a focus on improving both emotional and functional outcomes.